The Problem of Practice Dissertation: Matching Program Goals, Practices, and Outcomes - Belzer, Alisa; Axelrod, Tali; Benedict, Cathleen; Jakubik, Tara; Rosen, Michelle; Yavuz, Olcay (The EdD and the Scholarly Practitioner(HC), 2016)
The purpose of this book is to highlight the efforts of the members of the Carnegie Project on the Education Doctorate (CPED) to prepare Scholarly Practitioners in the field of education leadership. The volume is edited by Jill Alexa Perry, Executive Director of CPED, a consortium of 86 schools of education in the US, Canada and New Zealand. CPED is a collaboration of faculty working together since 2007 to re‐envision professional practice preparation in education. Contributing authors include faculty and graduates from CPED‐influenced programs. Faculty members highlight the need to rethink and strengthen all aspects of doctoral level preparation for practitioners, the expanded and enhanced role of research, inquiry and the dissertation in practice, and discuss the implications these changes have on university schools of education. Students and graduates, who face pressing educational issues in their daily lives, reflect on the impact their EdD program has had on their professional practice.
Keywords: dept.edl

Using educator characteristics on attitudes toward inclusion to drive professional development - Gregory, Jess L.; McCoy, T.; Baker, M.; Fedigan, A. (Journal of Advances in Education Research, 2016)
Keywords: dept.edl

Constructing Your Dissertation: A Guide for Students as They Begin Their Doctoral Research - Gregory, Jess L. (CreateSpace, 2016)
Keywords: Authorship; Academic writing; Dissertations, Academic; dept.edl; faculty_collection

Exploring the impacts of school reforms on underrepresented urban students’ college persistence - Yavuz, Olcay (Educational Research and Evaluation, 2016)
This longitudinal quantitative study investigates how participation in the Comprehensive College Readiness Access and Success Program (CCRASP) affects underrepresented urban students’ college persistence. Results revealed that CCRASP participation was associated with higher percentages of students enrolling in both 2- and 4-year colleges as sophomore students. As school leaders and policy makers seek to make all urban students college and career ready, these findings further solidify current urgencies to re-visit K–12 student academic and counselling services. It also provides school leaders and educators with practical information and reform ideas to improve underprivileged students’ persistence and success. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Research-supported school reforms; at-risk students; college persistence; dept.edl; programme evaluation

Pre-service teachers identify connections between teaching-learning and literacy strategies - Liu, Kimy; Robinson, Quintin; Braun-Monegan, Jenelle (Journal of education and training studies, 2016)
Keywords: dept.edl

Curriculum mapping in higher education: a case study and proposed content scope and sequence mapping tool - Arafeh, Sousan (Journal of Further and Higher Education, 2016)
Best practice in curriculum development and implementation requires that discipline-based standards or requirements embody both curricular and programme scopes and sequences. Ensuring these are present and aligned in course/programme content, activities and assessments to support student success requires formalised and systematised review and development processes. These processes are not always in play in higher education, however. Using a descriptive qualitative case study strategy, this article shares how policy outcomes within intermediate and superintendent certification, sixth-year and Ed.D. doctoral courses and programmes at a state university were reviewed, mapped and assessed using an evidence-based curriculum analysis model and tool that mapped standards and outcomes from course syllabus data. Strengths and weaknesses of this approach are discussed and it is suggested that the field might benefit from a curriculum mapping and analysis method that also considers content coverage. A Course-Level Content Scope and Sequence Mapping Tool, developed to map content scope and sequence alongside standards or outcomes mapping, is presented for consideration and testing. The ability to assess and improve curriculum is only as good as the conceptual frameworks, methods and tools available. This critical case study is one effort to advance the field by drawing attention to the importance of curricular content mapping. The study should be of interest to higher education staff, researchers and accreditors concerned with postsecondary programmes and their curricular scope and sequence coherence, quality and improvement. © 2015 UCU.
Keywords: Curriculum; content; content mapping; curricular content; curricular scope and sequence; curriculum mapping; curriculum mapping tool; dept.edl; educational leadership; higher education; policy; programme coherence

Provoking perspectives of creativity and innovation in leadership: innovation, accountability, and the human side of change - Gregory, Jess L (Journal of Leadership Studies, 2016)
Keywords: dept.edl; peer-reviewed

Building Social Capital from the Inside Out: Leveraging Intrapower (Personal Capital) - Haynes, Norris M. (Social Capital and Community Well-Being : The Serve Here Initiative, 2016)
In this writer’s view, the building of social capital starts with the development of personal individual capital. The author posits that an individual may not be optimally effective in building meaningful social relationships and networks, or in influencing results in one’s community that serve the individual and others well, unless the individual has the prerequisite personal attributes and skillsets to do so. Therefore, in this chapter, the author identifies four key personal capital attributes that he sees as foundational to the building of social capital from the inside out. The dynamic synergistic interface among these four core attributes (Control, Empathy, Awareness, and Resolve), is referred to in this chapter as “Intrapower that is seen as a potent facilitative force in the effective building of social capital.
Keywords: Achievement motivation; Civic engagement; Mindfulness; Resilience; Self-awareness; Self-control; Self-regulation; Social & emotional; Youth development; dept.edl